Bacteria Associated with Diarrhoea in Children in Khartoum State, Sudan 2006 - M. N., Hemidan; M.T, Shigidi; Y.H, Ali (Gezira Journal of Health Sciences, 2008)
This study was carried out to  identify enterobacteria in children suffering from diarrhoea in Khartoum State (Khartoum and Khartoum North) . Samples of diarrhoeal stool were collected  during the period from May to June 2006 from 60 children aged between 4 months to 5 years suffering from diarrhoea .              Isolated bacteria were identified on the basis of their cultural and biochemical characteristics and included the following species : Escherichia coli and Salmonella typhi from 5 specimens , S. paratyphi from 5 specimens , S. typhimurium from 4 specimens , Shigella  dysenteriae from one specimen , Sh. Flexneri from 2 specimens, Sh.boydii  from one specimen , Proteus vulgaris  from 2 specimens , Klebsiella pneumoniae  from 4 specimens , K. rhinoschermatis from 2 specimens and  Pseudomonas aeruginosa  from 6 specimens .  The susceptibility of isolated bacteria to some antibiotics using the  multi disk method was variable.